Natural resistance-associated macrophage protein 1 gene polymorphisms in thalassemia patients with tuberculosis infection - Mohammad Ghozali; Sari Puspa Dewi; Reni Ghrahani; Ani Melani Maskoen; Lelani Reniarti; Edhyana Sahiratmadja; Tri Hanggono Achmad (Paediatrica Indonesiana, 2016)
that needs regular blood transfusions leading to accumulation of iron in the cells. This iron overload level in macrophage might cause intracellular bacteria, particularly Mycobacterium tuberculosis (MTB) to multiply. Polymorphisms in natural resistance-associated macrophage protein 1 (NRAMP1), a metal transporter across the phagosome membrane, play important role in regulating iron, which is also needed by MTB. Increased iron in thalassemia patients may have an increased potential risk for TB.Objective To compare natural resistance-associated macrophage protein 1 (NRAMP1) gene polymorphisms (INT4, D543N, and 3’UTR) in thalassemia patients with and without tuberculosis (TB) infection.Methods A cross-sectional measurement of NRAMP1 genetic polymorphisms was performed in pediatric thalassemia patients with TB (n=40) and without TB (n=50). Iron status including serum iron, total iron-binding capacity (TIBC), and ferritin, was compared between the two groups. The NRAMP1 genetic polymorphisms were analysed using polymerase chain reaction/restriction fragment length polymorphism (PCR/RFLP). Allelic and genotypic distributions of each polymorphism were assessed for possible associations with TB infection.Results Mean serum iron and TIBC in thalassemia patients with TB were higher compared to thalassemia patients without TB (mean serum: 166.26 vs. 134.92 μmol/L, respectively; P=0.026) and (mean TIBC: 236.78 vs. 195.84 μmol/L, respectively; P=0.029). In thalassemia patients with TB, we observed significantly higher frequency of the C allele in INT4 (10% vs. 2%, respectively; OR=5.44; 95%CI 1.1 to 26.4; P=0.02) and the TGTG deletion allele (78.8% vs. 51%, respectively; OR=3.56; 95%CI 1.83 to 6.9; P=0.0002) in 3’UTR polymorphisms than in thalassemia patients without TB. There were no significant differences in distributions of the A allele between TB and non-TB groups (16.3% vs. 15%, respectively; P=0.84) or the GA genotype (32.5% vs. 30%, respectively; P=0.79) in D543N.Conclusion The NRAMP1 polymorphisms are known to be associated with major gene susceptibility to TB, and in our thalassemia patients this association is even more pronounced.